2020
DOI: 10.1186/s12885-020-06756-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of transcript expression patterns improves survival prediction in multiple cancers

Abstract: Background: Long-term survival in numerous cancers often correlates with specific whole transcriptome profiles or the expression patterns of smaller numbers of transcripts. In some instances, these are better predictors of survival than are standard classification methods such as clinical stage or hormone receptor status in breast cancer. Here, we have used the method of "t-distributed stochastic neighbor embedding" (t-SNE) to show that, collectively, the expression patterns of small numbers of functionally-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Transcripts used were those from Figure 2 , A and B and Refs. ( 35 ) and ( 36 )). FPKM-UQ values were obtained from the Genomic Data Commons-PANCAN dataset via the University of California Santa Cruz Xenabrowser ( xena.ucsc.edu ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts used were those from Figure 2 , A and B and Refs. ( 35 ) and ( 36 )). FPKM-UQ values were obtained from the Genomic Data Commons-PANCAN dataset via the University of California Santa Cruz Xenabrowser ( xena.ucsc.edu ).…”
Section: Resultsmentioning
confidence: 99%
“…F, cervical squamous cell carcinoma (CESC)/endocervical adenoma carcinoma. G, the average expression of transcripts encoding glycolytic enzymes ( 35 , 36 ) was obtained from each of the aforementioned favorable and unfavorable survival cohorts. p values were determined using Welch's t test.…”
Section: Resultsmentioning
confidence: 99%
“…Additional layers of complexity among members of the Extended Myc network have recently been identified with machine learning-based dimensionality reduction techniques such as t-SNE or UMAP that simultaneously compared the relationships among all Extended Myc Network member transcripts [405,406]. These studies showed most cancers to be comprised of 2-5 distinct clusters of Extended Myc Network transcripts that had prognostic value beyond that afforded by standard whole transcriptome profiling or the examination of single transcripts such as those depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these methods have also been shown to capture the heterogeneity of large-scale bulk RNA-seq [ 91 ]. Applied to thousands of cancer transcriptomes, t-SNE revealed small gene signatures correlating with long-term survival in the majority of tumor types [ 92 ].…”
Section: Managing the Heterogeneity Of Cancer Transcriptomesmentioning
confidence: 99%